European West Coast atmospheric rivers: A scale to characterize strength and impacts - Jorge Eiras-Barca; Alexandre M. Ramos; Iago Algarra; Marta Vázquez; Francina Dominguez; Gonzalo Miguez-Macho; Raquel Nieto; Luis Gimeno; Juan Taboada; F. Martin Ralph (Weather and Climate Extremes, 2021)
This manuscript applies the recently-created atmospheric river intensity and impacts scale (AR Scale) to the European continent. The AR Scale uses an Eulerian perspective based solely upon the time series of integrated vapor transport (IVT) over a given geographic location (often represented by a model or reanalysis “grid cell”). The scale assigns events with persistent, strong IVT at that location to one of five levels (AR1 to AR5), or if the IVT is too weak or short-lived it is determined not to be an AR. AR1 events are primarily beneficial, AR2, 3 and 4 include a mix of beneficial and hazardous impacts, while AR5s are primarily hazardous. The frequency of occurrence, the associated probability of anomalous precipitation and the amount of precipitation explained by each AR rank are provided across Europe for the extended winter season (from October through March). AR1 and AR2 events are the most frequent and explain most of the observed precipitation, but they are associated with a low probability of extreme rainfall. Although AR3, AR4 and AR5 events are much less frequent, and normally provide a smaller fraction of annual precipitation, they are associated with a high probability of extreme rainfall. These results show remarkable variability among the different regions of the European continent. This manuscript also provides an AR detection catalog over Europe for the period 1980–2019, and a simplified version of the algorithm used to rank the events from AR1 to AR5.